'Original Sin,' Balance Sheet Crises, and the Roles of International Lending - Zettelmeyer, Jeromin (IMF Working Papers; Working Paper ;, 2002)
We present a stylized framework which encompasses a variety of "balance sheet approaches" to currency crises that have been suggested in the literature, and analyze their policy implications. The common theme is that currency and maturity mismatches in private sector balance sheets constrain the capacity of monetary and fiscal policies to deal with self-fulfilling capital account crises, and generate a role for international crisis lending. International lending could be used to back domestic last-resort lending to banks, or to loosen fiscal constraints. Provided they have a sound fiscal position in normal times, this can make countries immune to self-fulfilling crises.